An NHC‐Stabilized H2GeBH2 Precursor for the Preparation of Cationic Group 13/14/15 Hydride Chains. Issue 3 (24th November 2021) - Ackermann, Matthias T.; Seidl, Michael; Wen, Fuwei; Ferguson, Michael J.; Timoshkin, Alexey Y.; Rivard, Eric; Scheer, Manfred
Abstract: The synthesis, characterization and reactivity studies of the NHC‐stabilized complex IDipp ⋅ GeH2 BH2 OTf (1 ) (IDipp=1, 3‐bis(2, 6‐diisopropylphenyl)imidazolin‐2‐ylidene) are reported. Nucleophilic substitution of the triflate (OTf) group in 1 by phosphine or arsine donors provides access to the cationic group 13/14/15 chains [IDipp ⋅ GeH2 BH2 ERR 1 R 2 ] + (2 E=P; R, R 1 =H; R 2 = t Bu; 3 E=P; R=H; R 1, R 2 =Ph; 4 a E=P; R, R 1, R 2 =Ph; 4 b E=As; R, R 1, R 2 =Ph). These novel cationic chains were characterized by X‐ray crystallography, NMR spectroscopy and mass spectrometry. Moreover, the formation of the parent complexes [IDipp ⋅ GeH2 BH2 PH3 ][OTf] (5 ) and [IDipp ⋅ GeH3 ][OTf] (6 ) were achieved by reaction of 1 with PH3 . Accompanying DFT computations give insight into the stability of the formed chains with respect to their decomposition. Abstract : The NHC‐stabilized compound IDipp ⋅ GeH2 BH2 OTf was synthesized. Reactivity studies on this novel building block with different phosphines and AsPh3 showed its potential to serve as an ideal precursor for unprecedented cationic group 13/14/15 chain compounds. In addition, a reaction with PH3 leads to the formation of the parent hydrides [IDipp ⋅ GeH2 BH2 PH3 ][OTf] and [IDipp ⋅ GeH3 ][OTf].